Comparative Analysis of Physical Carcass Composition of Male and Female Bali Cattle - Ni Made Ayu Gemuh Rasa Astiti; Ida Ayu Surasmi; Ye Saya Wadu; I Putu Wisnu Wibawa Putra (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Carcass meat is a highly nutritious livestock product recognized as a source of complete and balanced nutrition for humans, as it contains carbohydrates, proteins, fats, minerals, and vitamins essential for health. This study aims to analyze and compare the physical carcass composition of male and female Bali cattle. Bali cattle are a local Indonesian breed with significant potential in the livestock industry; however, information on the carcass composition of male and female Bali cattle remains limited. The study employs survey and interview methods, as well as a literature review. The research sample consists of 20 male and 20 female Bali cattle aged 2–3 years. The physical carcass composition variables include measurements of carcass weight, carcass percentage, and physical carcass components (meat, skin, and bone). The study results are expected to provide data on the physical composition of male and female Bali cattle carcasses, serving as a reference for the development of the Bali cattle livestock industry. Furthermore, this research aims to contribute to improving Bali beef quality and increasing farmers' income. Descriptive and comparative statistical analyses are used to identify differences in the physical composition of the carcass between male and female Bali cattle. The findings are presented in tables, graphs, and narrative descriptions and disseminated through scientific journals and national seminars. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 8: Decent Work and Economic GrowthSDG 12: Responsible Consumption and ProductionSDG 15: Life on Land